The Improvement of Heart Histopathology of Hypercholesterolemic Mice using Sidempuan Salacca (Salacca sumatrana) Vinegar - Atifah, Yusni; Az zahra, Firda; Helendra, Helendra; Lubis, Jalilah Azizah; Afrilliana, Friska (Biology, Medicine, & Natural Product Chemistry, 2025)
Hypercholesterolemic, a condition characterized by excess cholesterol content, can lead to coronary heart disease, atherosclerosis, and high-risk heart tissue degeneration. Current drugs, like simvastatin and pravastatin, focus on lowering cholesterol levels without addressing tissue degeneration. This study aimed to determine the effectiveness of sidempuan salacca vinegar in improving cardiac tissue degeneration in hypercholesterolemic mice. The experimental research involved two groups, the treatment group given different doses of sidempuan salacca vinegar and the control group. Histopathological observations showed improvement in cardiac tissue degeneration in hypercholesterolemic mice after treatment with salacca vinegar. The administration of salacca vinegar could serve as a reference for developing alternative hypercholesterolemic drugs that address both cholesterol levels and heart degeneration.